INSPIRASI FILM “DREAM” DALAM PERWUJUDAN FABRIC MANIPULATION DI BIDANG FASHION - Zahro, Siti; Nadyne Feliciona Towoliu, Steffie; Mustikasari, Hany (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
Currently, humans are increasingly moving towards individualism. This is due to the influence of technological developments and trust issues in society. Therefore, relationships between humans need to be built and maintained in social life for the sustainability of interdependent and bound life. Furthermore, the idea of ​​this research was inspired by the film "Dream", which is about the relationship of togetherness that is established between humans through a Homeless World Cup event. The aim is to describe the translation of inspiration from togetherness into a fashion and fabric manipulation for a cloth accessory. The research method chosen is quasi-qualitative to support the design and manufacturing process of fabric manipulation. The data analysis technique uses a descriptive technique to describe the results of the questionnaire and a simple research analysis to describe the results of textile manipulation. The results of the study showed that the indicators for making fabric manipulation are based on togetherness, unity, and solidarity. Furthermore, the fabric manipulation produced is in the form of fabric weaving and macrame, with a color palette of natural, neutral, and warm colors. Fabric manipulation and color palette are supported by designs that depict cohesion and harmony. Thus, it is forming a ready-to-wear fashion collection with high value and selling power.